Quality and stability of co-amoxiclav products in the Yemeni market - Al-Tahami, Khaled (Journal of Chemical and Pharmaceutical Research, 2014)
Drug cost is still one of the major obstacles for health care in the world. A valid option for overcoming this problem is by generic substitution. Yet, the problem of quality emerges as cheap prices are often associated with poor quality. The stability of such medications is also questionable especially if storage conditions were not provided. Many reconstituted antibiotic suspension is to be kept refrigerated in order to get the optimal benefit from the drug. This study compared four products present in the Yemeni market containing amoxicillin and clavulanic acid in terms of quality control tests carried out to ensure the quality of their products. The stability of original productwas evaluated in terms of the effect of storage conditions and type of water use. It was found that the quality of the four products tested was comparable. It was also confirmed that the use of tap water has a degrading effect on the stability of both ingredients, but it has more effect on the degradation of clavulanic acid. Similar results were found regarding the storage of these products in room temperature. We conclude that there should be more emphasis on the principles of pharmacoeconomics regarding the ethical prescribing practice where generic substitution is considered for economical factors. We also recommend that products should be stored as instructed and the patients should be informed to use bottled water for reconstitution of such products.